2017
DOI: 10.1186/s12872-017-0544-z
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean dietary quality index and dietary phytochemical index among patients candidate for coronary artery bypass grafting (CABG) surgery

Abstract: BackgroundThe aim of the present research was to evaluate the relationship between Mediterranean dietary quality index (Med-DQI) and dietary phytochemical index (DPI) with metabolic risk factors of cardiovascular disease in candidates for coronary artery bypass graft (CABG) surgery.MethodsThis was a cross-sectional study on 454 patients aged 35–80 years as candidates of CABG and hospitalized in Tehran Heart Center. Anthropometric and demographic characteristics were obtained from all participants and a 138-ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…Accordingly, a 125-subject sample size was determined for the study (125 in each group). We also assumed 20% loss (125 + 25) and as men with CAD are twice as women (150 + 300), the final sample size of 450 was considered for the study [ 25 – 27 ]. Reasons for drop-out or exclusion were incomplete dietary questionnaires ( n = 1), and incomplete demographic questionnaires ( n = 5).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, a 125-subject sample size was determined for the study (125 in each group). We also assumed 20% loss (125 + 25) and as men with CAD are twice as women (150 + 300), the final sample size of 450 was considered for the study [ 25 – 27 ]. Reasons for drop-out or exclusion were incomplete dietary questionnaires ( n = 1), and incomplete demographic questionnaires ( n = 5).…”
Section: Methodsmentioning
confidence: 99%
“…The MD is characterized by a favorable lipid profile for cardiovascular function, with a high percentage of unsaturated fatty acids from olive oil and nuts [21]. On the other hand, the MD, due to its high content in plant-derived foods, is an extraordinary source of phytochemicals and also ensures a high intake of fibers [22,23]. Key foods of the MD, such as olive oil, oily fish, nuts, yoghurt, several fruits, spices, and herbs, are considered functional foods due to their nutraceutical content [24].…”
Section: Healthy Properties Of Mediterranean Dietmentioning
confidence: 99%
“…Previous studies also revealed the association between 6P21 rs2010963 genotype with severity and extent of coronary artery disease [27,28]. In fact, health dietary choices might be inhibitors of 6P21 rs2010963 gene expression [29] while inappropriate dietary habit might induce it [30,31]. The CC genotype and the C allele of 6P21 rs2010963 gene is considered to be the main risk factor of metabolic disorders, cardiovascular events; Nia SA et al showed that C allele of rs2010963 polymorphism was related to increase risk for CAD and to 5-year cardiovascular mortality in Iranian population [32].…”
Section: Discussionmentioning
confidence: 92%